Progress in antiandrogen design targeting hormone binding pocket to circumvent mutation based resistance - Tian, Xiaohong; He, Yang; Zhou, Jinming (Frontiers in Pharmacology, 2015)
Androgen receptor (AR) plays a critical role in the development and progression of prostate cancer (PCa). Current clinically used antiandrogens such as flutamide, bicalutamide, and newly approved enzalutamide mainly target the hormone binding pocket (HBP) of AR. However, over time, drug resistance invariably develops and switches these antiandrogens from antagonist to agonist of the AR. Accumulated evidence indicates that AR mutation is an important cause for the drug resistance. This review will give an overview of the mutation based resistance of the current clinically used antiandrogens and the rational drug design to overcome the resistance, provides a promising strategy for the development of the new generation of antiandrogens targeting HBP.